Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 1 - Section 1.2 - Formulas and Percent - 1.2 Exercises: 35

Answer

$y=\dfrac{3}{2}x-3$

Work Step by Step

Using the properties of equality, in terms of $ y ,$ the given equation, $ \dfrac{1}{2}x-\dfrac{1}{3}y=1 ,$ is equivalent to \begin{array}{l}\require{cancel} 6\left(\dfrac{1}{2}x-\dfrac{1}{3}y\right)=(1)6 \\\\ 3x-2y=6 \\\\ -2y=-3x+6 \\\\ y=\dfrac{-3}{-2}x+\dfrac{6}{-2} \\\\ y=\dfrac{3}{2}x-3 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.